Town Green area, detail of exterior view of Pierce Hall, Brookline, Massachusetts. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
Originally built in 1824 as a two-story Town House to hold a school, a meeting hall, and town offices. The building lost its role with the construction of a new Town Hall on Washington Street in 1844. Bought by the First Parish Church in 1890, it was named Pierce Hall in honor of the Rev. John Pierce, and incorporated into the church in 1906. (Source: Community Walk website).; Caption on image: Town Green Area (2) Pierce Hall, ext, det Walking Tour 1825.; Binder Number 4. Pocket Number: 11.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.